2020
DOI: 10.1063/5.0027687
|View full text |Cite
|
Sign up to set email alerts
|

Identification of surface and volume hot-carrier thermalization mechanisms in ultrathin GaAs layers

Abstract: Hot-carrier solar cells offer the opportunity to harvest more energy than the limit set by the Shockley-Queisser model by reducing the losses due to the thermalization of photo-generated carriers. Previous reports have shown lower thermalization rates in thinner absorbers, but the origin of this phenomenon is not precisely understood. In this work, we investigate a series of ultrathin GaAs absorber layers sandwiched between AlGaAs barriers and transferred on host substrates with a gold back mirror. We perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…This effect indicates that by considering the amount of the thermalized power above the absorber band edge, it is possible to define a thermalization coefficient, which evaluates the performance of the sample in inhibiting the thermalization loss and is not dependent on the excitation wavelength. Similar behavior has been recently observed by Giteau et al 17 in thin GaAs absorbers and its origin is discussed in detail.…”
Section: Resultssupporting
confidence: 88%
“…This effect indicates that by considering the amount of the thermalized power above the absorber band edge, it is possible to define a thermalization coefficient, which evaluates the performance of the sample in inhibiting the thermalization loss and is not dependent on the excitation wavelength. Similar behavior has been recently observed by Giteau et al 17 in thin GaAs absorbers and its origin is discussed in detail.…”
Section: Resultssupporting
confidence: 88%
“…We show this by extracting carrier temperatures using two generic experimental procedures frequently used, namely (i) extracting a temperature from the heat transfer between carriers and phonons (measured via, e.g., a floating thermal probe or a thermocouple 51,52 ), and (ii) by fitting the photoluminescence (PL) spectra. [53][54][55] These two temperatures are shown to be very different from one another.…”
Section: Introductionmentioning
confidence: 87%
“…We then extract the steady-state electron and hole temperatures, T e and T h , respectively, by adapting two generic experimental procedures frequently used, (i) from the exchange of power between the electron (hole) sub-systems and the phonons (see Supplementary Section S6), 51,52 and (ii) from the steady-state PL spectra (see Supplementary Section S7). [53][54][55]…”
Section: Macroscopic Formulation -Energy and Number Conservationmentioning
confidence: 99%
“…In 1996, Langot et al investigated the slowed hot electron thermalization due to the hot phonon effect in bulk GaAs by using femtosecond absorption saturation techniques at room temperature. 72 A quantitative analysis on the hot phonon effect was carried out by changing either the individual excess energy of the photoexcited carriers or the carrier density in the moderate range from 41 This work shows an affine dependence with the thickness of GaAs absorber, leading to the identification of distinct volume and surface contributions to thermalization. It is confirmed that volume thermalization is linked to LO phonon decay.…”
Section: Arsenides and Their Alloysmentioning
confidence: 99%